Ellagic acid improves endogenous neural stem cells proliferation and neurorestoration through Wnt/β‐catenin signaling in vivo and in vitro. Issue 3 (2nd December 2016) - Liu, Qing‐Shan; Li, Shu‐Ran; Li, Keqin; Li, Xu; Yin, Xiaoying; Pang, Zongran
Abstract : Ellagic acid (EA) administration can improve brain injury outcomes and increase the proliferation of NSCs through the Wnt/β‐catenin signaling pathway. To the best of our knowledge, these results represent new insights on the mechanisms of the brain cell protective activity of EA. EA may be used to help treat nerve dysfunction, neurodegenerative disease and aging. Abstract : Scope: The aim of this study is to research the effects of the polyphenol ellagic acid (EA) on brain cells and to explore its mechanism of action, and to evaluate whether EA can be safely utilized by humans as a functional food or therapeutic agent. Methods and results: A photothrombosis‐induced model of brain injury in rats was created, and EA was administered intragastrically to rats on 7 consecutive days post‐venous ischemia. An oxygen–glucose deprivation and re‐perfusion model was established in neural stem cells in order to research the effects on proliferation after 2 days of EA treatment in vitro. The administration of EA improved the rats' nerve‐related abilities, remedied infarct volumes and morphological changes in the brain, and enhanced the content of nestin protein in the brain semidarkness zone. The proliferation of NSCs and the expression of β‐catenin and Cyclin D1 genes were also increased in primary cultured NSCs. Conclusions: EA administration can improve brain injury outcomes and increase the proliferation of NSCs through the Wnt/β‐catenin signaling pathway. The presented results represent new insights on the mechanisms of the brain cell protective activity of EA. Thus, EA may be used in functional foods or medicines to help treat nerve dysfunction, neurodegenerative disease and aging.